2013
DOI: 10.1073/pnas.1303687110
|View full text |Cite
|
Sign up to set email alerts
|

X-linked microtubule-associated protein, Mid1, regulates axon development

Abstract: Opitz syndrome (OS) is a genetic neurological disorder. The gene responsible for the X-linked form of OS, Midline-1 (MID1), encodes an E3 ubiquitin ligase that regulates the degradation of the catalytic subunit of protein phosphatase 2A (PP2Ac). However, how Mid1 functions during neural development is largely unknown. In this study, we provide data from in vitro and in vivo experiments suggesting that silencing Mid1 in developing neurons promotes axon growth and branch formation, resulting in a disruption of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(47 citation statements)
references
References 35 publications
(41 reference statements)
1
40
0
1
Order By: Relevance
“…Despite previous evidence showing that contralateral callosal mistargeting can be affected in isolation from midline defects in mice (Mizuno et al, 2007;Lu et al, 2013;Suárez et al, 2014b), no studies have thus far assessed the behavioural consequence of disrupted contralateral targeting in isolation. However, using diffusion magnetic resonance imaging (dMRI) and tractography, it has been demonstrated that contralateral callosal targeting can be highly variable and misregulated in humans with gross structural malformations of the corpus callosum at the midline (Tovar-Moll et al, 2007;Wahl et al, 2009;Bénézit et al, 2015).…”
Section: Contralateral Callosal Targeting In Humansmentioning
confidence: 97%
See 4 more Smart Citations
“…Despite previous evidence showing that contralateral callosal mistargeting can be affected in isolation from midline defects in mice (Mizuno et al, 2007;Lu et al, 2013;Suárez et al, 2014b), no studies have thus far assessed the behavioural consequence of disrupted contralateral targeting in isolation. However, using diffusion magnetic resonance imaging (dMRI) and tractography, it has been demonstrated that contralateral callosal targeting can be highly variable and misregulated in humans with gross structural malformations of the corpus callosum at the midline (Tovar-Moll et al, 2007;Wahl et al, 2009;Bénézit et al, 2015).…”
Section: Contralateral Callosal Targeting In Humansmentioning
confidence: 97%
“…Factors that have been shown to regulate this process include Slit2 (Shu et al, 2003a) and Wnt5a/Ryk (Keeble et al, 2006;Hutchins et al, 2011 (Mizuno et al, 2007;Lu et al, 2013;. This suggests that, while callosal malformations are diagnosed from gross midline imaging, defects arising from isolated errors in contralateral targeting may remain undiagnosed in humans.…”
Section: Midline Crossingmentioning
confidence: 99%
See 3 more Smart Citations